Aligning Practice Data and Institution-specific CPD: Medical Quality Management as the Driver for an eLearning Development Process. Issue 1 (1st January 2020) - Archibald, Douglas; Burns, Joseph K.; Fitzgerald, Michael; Merkley, Véronique French
ABSTRACT: For hospital physicians, alignment of Continuing Professional Development (CPD) with quality improvement efforts is often absent or rudimentary. The purpose of this study was to evaluate a CPD development process that created accessible learning opportunities and aligned CPD with practice data. We conducted a chart audit to identify patient safety and quality of care issues within the institution, then established an eLearning approach that supported quick and cost effective development of high-quality interactive CPD opportunities. We tested a pilot module on the management of common infections in sub-acute care settings with fifteen (68%) residents and three staff physicians to evaluate the approach. One resident and three staff agreed to a follow-up interview. The satisfaction survey indicated that participants felt the content was generally appropriate and the module well designed. Significant improvements to knowledge were reported in the multi-drug resistance (Mean Difference = 25%, p = 0.002), infection management (MD = 32%, p < 0.001), and cellulitis risk factor (MD = 22%, p = 0.02) questions, as well as in the overall score (MD = 19%, p < 0.001). In terms of confidence in their answers, the mean rating pre-module was 3.17, rising significantly to 3.92 post-module (p < 0.001). In this way, collaboration between quality management and education committees allowed for the development of relevant CPD for physicians, with eLearning providing a timely and accessible way to deliver training on emerging issues.